ZBP1 and heatstroke - Li, Fanglin; Deng, Jiayi; He, Qiuli; Zhong, Yanjun (Frontiers in Immunology, 2023)
Heatstroke, which is associated with circulatory failure and multiple organ dysfunction, is a heat stress-induced life-threatening condition characterized by a raised core body temperature and central nervous system dysfunction. As global warming continues to worsen, heatstroke is expected to become the leading cause of death globally. Despite the severity of this condition, the detailed mechanisms that underlie the pathogenesis of heatstroke still remain largely unknown. Z-DNA-binding protein 1 (ZBP1), also referred to as DNA-dependent activator of IFN-regulatory factors (DAI) and DLM-1, was initially identified as a tumor-associated and interferon (IFN)-inducible protein, but has recently been reported to be a Z-nucleic acid sensor that regulates cell death and inflammation; however, its biological function is not yet fully understood. In the present study, a brief review of the main regulators is presented, in which the Z-nucleic acid sensor ZBP1 was identified to be a significant factor in regulating the pathological characteristics of heatstroke through ZBP1-dependent signaling. Thus, the lethal mechanism of heatstroke is revealed, in addition to a second function of ZBP1 other than as a nucleic acid sensor.